Comprehensive Nursing Care and Clinical Management of Patients Undergoing Hemorrhoidectomy Across the Preoperative Intraoperative and Postoperative Phases - Madkhali, Maryam Ahmad; Basmah Mohammad Jahfley; Talbah Mohammedl Lshaq; Ghadah Ayed Al Malki; Fatimah Ahmad Sadly; Maha Saleem Alammar; Abeer Sweilem Alharthy; Safyah Hassan Madkhali; Eidah Khalaf Al-Bakhit; Maitha Khalaf Mahmmed Albkhaeit; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Hemorrhoidal disease is one of the most common anorectal disorders encountered in clinical practice, with surgical intervention required in a subset of patients with advanced or refractory disease. Hemorrhoidectomy remains the definitive treatment for grade III and IV hemorrhoids; however, optimal patient outcomes depend heavily on comprehensive perioperative nursing care and interprofessional collaboration. Aim: This article aims to describe evidence-based nursing care and clinical management strategies for patients undergoing hemorrhoidectomy across the preoperative, intraoperative, and postoperative phases. Methods: A narrative review of current clinical guidelines, randomized controlled trials, and meta-analyses was conducted to evaluate surgical techniques, perioperative preparation, complication management, and nursing interventions related to hemorrhoidectomy. Emphasis was placed on multimodal pain management and interprofessional roles. Results: Surgical hemorrhoidectomy, particularly closed techniques, demonstrated high efficacy with low recurrence rates. Effective nursing interventions, including patient education, pain assessment, wound care, and bowel management, significantly reduced complications such as bleeding, urinary retention, and anal stenosis. Multimodal analgesia improved postoperative comfort and recovery. Conclusion: Comprehensive nursing care combined with coordinated interprofessional management plays a critical role in optimizing patient safety, reducing complications, and enhancing recovery following hemorrhoidectomy.